Statistical Approach of Knowledge Management for Improvement of Hospitalized Management. (February 2020) - Arini, M.; Muhammad, A.F.; Listiowati, E.
Abstract: Elderly quality of life (QoL) is affected by the decline in health status, and vice versa. The purpose of this study was to find out whether there were differences between before and after the provision of Islamic spiritual care services (ISC) to elderly patients. This study was a quasi-experimental research design with pre-test & post-test assessments. A sample of 106 elderly patients at PKU Muhammadiyah Gamping Hospital Yogyakarta with an age range of 60-70 years was consecutively selected by inclusion criteria. The QoL was measured using the validated Indonesian version of OPQOL-Brief questionnaire. Data were analyzed using the Wilcoxon test because of the abnormality distribution. There was an increase of the means of QoL after the ISC provision by the p-value=0.000. It is concluded from this study that elderly's QoL had significant differences between before and after the ISCS provision. The results of the study indicate that ISC is potential to be developed in order to improve the QoL of elderly patients.